A Study on Solar Photovoltaic Array Surface Morphology Variation in Sandy Area Based on Wind Tunnel Test - Tang Guodong; Meng Zhongju; Gao Yong; Dang Xiaohong; Guo Jianying; Xing Ende (Shuitu baochi tongbao)
[Objective] The surface morphology changes and its relation with wind environment under wind regime disturbance by a solar photovoltaic array in a sandy area of the middle part of Kubuqi Desert, in order to provide a theoretical basis for determining a technical scheme to minimize wind and sand hazards at solar photovoltaic (PV) power stations. [Methods] Spatial distribution of surface erosion and deposition and characteristics of the surface morphology profile at five angles (0°, 45°, 90°, 135°, and 180°) between the solar PV array and the wind direction were analyzed by wind tunnel experiments. [Results] When the included angle between the solar PV array and the wind direction was ±90°, the surface erosion intensity was mainly moderate and severe, and deposition intensity was mainly mild. Surface erosion intensity was greatly reduced in the 3rd to 5th rows of panels because of sheltering effects. The erosion and deposition change law for all panel areas was similar at the ±45° angles. When the included angle was -45°, the surface erosion and deposition intensity were mainly mild and moderate. but severe deposition intensity occurred in a small area. When the included angle was -45°, the surface erosion intensity was mainly moderate and mild, and deposition intensity was mainly mild and moderate. The surface erosion and deposition intensity at the different included angles followed the order of 45°>90°>-45°>-90°>0°. As an example, when wind speed was 8 m/s, the surface erosion and deposition intensity were the smallest with the 0° angle, and the range of surface erosion and deposition was only 1.265 cm. The surface erosion and deposition intensity were the largest with the 45° angle, and the range of erosion and deposition reached 5.429 cm. In addition, when the absolute value of the included angle was equal and the sign was opposite, the wind and sand activity on the surface of the photovoltaic array was stronger when the included angle was positive than when it was negative. When the included angle was 45°, the surface erosion and deposition intensity was 1.566 times higher than that was -45°. When the included angle was 90°, the surface erosion and deposition intensity was 1.269 times higher than that was -90°. [Conclusion] The design of technical schemes to minimize wind and sand hazards at solar PV power stations in sandy areas should fully consider the prevailing wind direction conditions.